PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN TETAP DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. TEKAD KARYA PUTERA SITUBONDO - Khofifa, Siti; Arief, Mohammad Yahya; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the effect of work conflict and work stress on the performance of permanent employees with job satisfaction as an intervening variable at PT. Putera Situbondo's determination. The sampling technique that will be used in the study is the Non Probability Sampling technique by means of Total Sampling or saturated samples. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that work conflict has a positive and significant effect on job satisfaction, job stress has a positive and significant effect on job satisfaction, work conflict has a positive and significant effect on employee performance, job stress has a positive and significant effect on job satisfaction. Employee performance, job satisfaction has a positive and significant effect on employee performance, work conflict has a positive and significant effect on employee performance through job satisfaction, job stress has a negative and insignificant effect on employee performance through job satisfaction